Targeted nutritional intervention with enhanced recovery after surgery for carotid endarterectomy: A prospective clinical trial - Li, Yu-Qian; Qu, Xiao-Peng; Peng, Li-Wei; An, Jie-Yuan; Liu, Xin-Wei; Zhang, Yue; Wang, Chao; Jiang, Xue; Gao, Li; Li, Gang; Wang, Da-Li; Zhao, De-Chang; et al. (Frontiers in Nutrition, 2023)
Abstract Ischemic stroke is the most common cerebrovascular disease, and vascular obstruction is an important cause of this disease. As the main method for the management of carotid artery stenosis, carotid endarterectomy (CEA) is an effective preventive and treatment measure in ischemic cerebrovascular disease. This study aims to propose the application of a new enhanced recovery after surgery (ERAS) nutritional support regimen in CEA, which can significantly improve the perioperative nutritional status of patients. A total of 74 patients who underwent CEA were included and randomized into two groups: 39 patients received nutritional therapy with the ERAS protocol (ERAS group) and 35 patients received routine perioperative nutritional support (control group). Our results showed that the levels of major clinical and biochemical parameters (albumin, hemoglobin, creatinine, calcium and magnesium levels，etc.) in the ERAS group were significantly higher than in the control group after surgery (P < 0.05). Additionally, patients in the ERAS group had dramatically shorter postoperative length of stay and reflected higher mean satisfaction at discharge (P < 0.001). Moreover, no statistically significant differences were observed in postoperative complication rates and Mini-mental State Examination scores at discharge. The emergence of this neurosurgical ERAS nutritional support program can effectively intervene in perioperative nutritional status, and notably reduce postoperative hospital stays.